A comparison of single-vacuum-bag and double-vacuum-bag methods for manufacturing high-quality laminated composites - Mujahid, Y. (Springer Science and Business Media Deutschland GmbH, 2020)
Selection of an appropriate vacuum-bagging technique is critical for producing high-quality laminated composites. However, the comparative study among various choices of vacuum-bagging techniques is not readily available. This study investigates the contribution of various bagging techniques and laminate thicknesses in achieving lower void content. Six laminates were produced, and their contents of surface porosity and through-thickness void were evaluated. The lowest contents of surface porosity and through-thickness void are achieved using a double-vacuum-bagging technique, i.e., 0.04 and 0.5, respectively. The reduced void content is a result of the ballooning effect due to a pressure difference between the inner and outer bags. The laminate void content increased with an increase in thickness. The highest content of void is reported in the laminate with 3.2Â mm thickness, i.e., 0.79. This comparative study conclusively elucidates the importance of selecting appropriate processing parameters in reducing the formation of voids in laminated composites. Â© Springer Nature Singapore Pte Ltd 2020.